Usage of E-learning Tools in Self-education of Government Officers Involved in Global Trade Activities (Pedagogy of Higher and Secondary Education, 2018)
Triakina O.O., Pavlenko O.O., Volkova N.P., Kasim D.O. Usage of E-learning Tools in Self-education of Government Officers Involved in Global Trade Activities.The article concerns the issue of e-learning tools implementation, including the Customs Learning and Knowledge Community electronic platform designed by the World Customs Organization and the TradeFacilitation Implementation Guide case studies collected by the United Nations Economic Commission for Europe, into the self-education process of current government employees (within in-service training) and future public officers (within master’s programs) connected with international trade transactions. The authors give a description of the content and characteristical features of existing e-learning instruments related to training of professionals in Customs and trade fields as well as of certain tasks developed by the authors. The efficiency of the abovementioned e-learning tools has been experimentally proved in the paper, which has shown that these tools promote the growth of the professional competence of government officers and give a great opportunity for them to be involved in life-long learning to acquire various professional knowledge and skills
Keywords: e-learning tools; self-study; government officers; Customs Learning and Knowledge Community e-learning platform; case studies; interactive courses; self-education